The Cost of Quality: Organizational Financial Health and Program Quality. Issue 1 (2nd January 2019) - Bunger, Alicia C.; Despard, Mathieu; Lee, Madeline; Cao, Yiwen
ABSTRACT: Purpose : Nonprofit health and human service organizations (NPHSOs) encounter pressure to improve program quality to continue to secure financial resources. Yet, organizations also struggle to innovate, evaluate, and monitor quality absent sufficient resources. This study explores the relationship between NPHSOs' financial health and quality indicators. Methods : Quality indicators were measured in an online survey with leaders from 32 nonprofit children's behavioral health organizations within a Midwestern urban region. Survey responses were matched with financial health metrics extracted from publicly available IRS 990 forms from 2010 to 2014. Results : Organizations struggled to maintain adequate reserve levels, although those with more quality capacities had greater assets and growth in those assets. Discussion : Although financial health appeared to be related to quality, it is unclear whether quality attracts financial resources, or if financial reserves support quality. Conclusion : Continuing research and dialogue are needed to understand the financial implications of an increasing emphasis on quality.